A pilot evaluation of the 3gLM-R - A new supraglottic airway device - Michalek, Pavel; Jindrova, Barbora; Kriz, Petr; Stritesky, Martin; Sedlar, Martin (Advances in medical sciences, 2015)
INTRODUCTION: Supraglottic airway devices are designed for airway management during anaesthesia. The 3gLM is a novel device with a non-inflatable soft cuff and separate channels for gas delivery and drainage of gastric content. MATERIAL AND METHODS: This prospective observational study of the 3gLM, version R, size 4 in 40 adult patients scheduled for elective surgery, evaluated the insertion success rate at the 1st attempt as the primary outcome. Secondary aims included insertion parameters, such as total success rate, insertion time, oropharyngeal seal pressures, postoperative complications and a comparison between males and females. RESULTS: First attempt insertion success rate was 80% (70% in males, 90% in female patients, p=0.24), while total insertion success rate was 92.5% (85% in males, 100% in females, p=0.23). The oropharyngeal seal pressures were 27cmH2O, higher in females (29.4cmH2O) than in males (24.2cmH2O) - p=0.002. Postoperative complications were only temporary and included sore throat (24.3%), hoarseness (10.8%), pain on swallowing (10.8%) and minor tongue haematoma (2.5%). There was no difference in the incidence of postoperative complications between the genders apart from hoarseness. No aspiration of gastric contents or other long-term complications occurred in this cohort. CONCLUSIONS: The 3gLM exhibited oropharyngeal seal pressures adequate for the controlled ventilation in most patients. Size 4 of the device showed higher pressures in females than in men.
Keywords: Controlled ventilation; Pressure; Anesthesia, General; lidé; elektivní chirurgické výkony; tlak; mužské pohlaví; prospektivní studie; Elective Surgical Procedures; Female; Male; celková anestezie; Prospective Studies; 3gLM; Supraglottic airway device; Oropharyngeal seal pressure; ženské pohlaví; Humans